2019
DOI: 10.1080/00207721.2019.1567863
|View full text |Cite
|
Sign up to set email alerts
|

An improved adaptive online neural control for robot manipulator systems using integral Barrier Lyapunov functions

Abstract: Conventional Neural Network (NN) control for robots use radial basis function (RBF) and for n-link robot with online control, the number of nodes and weighting matrix increases exponentially, which requires a number of calculations to be performed within a very short duration of time. This consumes a large amount of computational memory and may subsequently result in system failure. To avoid this problem, this paper proposes an innovative NN robot control using a dimension compressed RBF (DCRBF) for a class of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 42 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…Based on Reference 37, we know that V0i$$ {V}_{0i} $$ satisfied positive definite, continuously differentiable, and radially unbounded properties in the set normalΩ=false{ei:false|eifalse|<ki,ki>0,i=1,2,,nfalse}$$ \Omega =\left\{{e}_i:|{e}_i|<{k}_i,{k}_i>0,i=1,2,\dots, n\right\} $$. Therefore, V0i$$ {V}_{0i} $$ is a valid Lyapunov function.…”
Section: Observer‐controller Designmentioning
confidence: 99%
“…Based on Reference 37, we know that V0i$$ {V}_{0i} $$ satisfied positive definite, continuously differentiable, and radially unbounded properties in the set normalΩ=false{ei:false|eifalse|<ki,ki>0,i=1,2,,nfalse}$$ \Omega =\left\{{e}_i:|{e}_i|<{k}_i,{k}_i>0,i=1,2,\dots, n\right\} $$. Therefore, V0i$$ {V}_{0i} $$ is a valid Lyapunov function.…”
Section: Observer‐controller Designmentioning
confidence: 99%
“…And the BLF is also widely used to deal with state constraints 17 and output constraints 18 . A symmetric integral BLF‐based controller is proposed for manipulators, 19 in which the full‐state constraint on the manipulators is achieved by setting preset boundaries on position and velocity by BLF, respectively. In work, 20 an ln‐type BLF‐based adaptive constraint control law is proposed for the flexible manipulator, in which the BLF sets boundaries on the angular position, angular velocity, boundary position, and boundary velocity to achieve full‐state constraints on the flexible manipulators.…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies showed the application of BLFs for full-state constraint systems in either regular (Brunovskii) or non-regular forms. [24][25][26] Nevertheless, the mentioned approaches offer asymptotic convergence of the system states, and in several cases, they are not robust against external perturbations. In spite their clear advantages, both control forms (TSM and NTSM) are not considering the given coordinate constraints which design a restricted working space within their mathematical form.…”
Section: Introductionmentioning
confidence: 99%